Continuous Enzymatic Synthesis of Lactulose in Packed-Bed Reactor with Immobilized Aspergillus Oryzae β-galactosidase - Vera-Vera, C (Elsevier Ltd, 2019)
Lactulose synthesis from fructose and lactose in continuous packed-bed reactor operation with glyoxyl-agarose immobilized Aspergillus oryzae β-galactosidase is reported for the first time. Alternative strategies to conventional batch synthesis have been scarcely explored for lactulose synthesis. The effect of flow rate, substrates ratio and biocatalyst-inert packing material mass ratio (MB/MIM) were studied on reactor performance. Increase in any of these variables produced an increase in lactulose yield (YLu) being higher than obtained in batch synthesis at comparable conditions. Maximum YLu of 0.6 g·g−1 was obtained at 50 °C, pH 4.5, 50% w/w total sugars, 15 mL·min−1, fructose/lactose molar ratio of 12 and MB/MIM of 1/8 g·g−1; at such conditions yield of transgalactosylated oligosaccharides (YTOS) was 0.16 g·g−1, selectivity (lactulose/TOS molar ratio) was 5.4 and lactose conversion (XLactose) was 28%. Reactor operation with recycle had no significant effect on yield, producing only some decrease in productivity. © 2018